Peran Badan Usaha Milik Desa (BUMDes) Terhadap Peningkatan Kesejaheraan Masyarakat Dalam Bidang Ekonomi - Hafiziah Nazira Putri; Sopyan Resmana; Haura Atthahara; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2022)
In Law Number 6 of 2014 concerning Villages, Village-Owned Enterprises are business entities whose capital is wholly or most of the capital owned by the village through direct participation originating from village assets which are separated from managing assets, services, and other businesses for an amount of - the welfare of the village community. This BUMDes was established at the initiative of the community and/or village government to utilize all economic potential, natural resources, and human resources in the village in order to improve the welfare of the village community. The purpose of this study was to determine the existence, role and impact of BUMDes for the welfare of the village community. In this study, researchers used descriptive research methods with a qualitative approach. The focus in this research is BUMDes in the village, how the participation of the village community. The result of this study is that the role of BUMDes in Tanjungbaru village in improving community welfare in the economic field has not been realized due to the lack of community participation and the lack of contribution from BUMDes administrators in managing and developing BUMDes in Tanjungbaru village.